2003
DOI: 10.1176/appi.ajp.160.1.172
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis C Among Psychiatric Patients in the Public Sector

Abstract: The prevalence of hepatitis C virus is high among psychiatric patients in the public sector. Much needs to be learned about the role of universal screening and effective techniques for primary prevention and antiviral treatment in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 7 publications
3
53
0
2
Order By: Relevance
“…Previous results showed that the rates of exposure to HBV and HCV infection among psychiatric patients were significantly higher than the estimated general population rates [17][18][19][20][21]. A study by Dinwiddie et al reported that 27.8% patients had HBsAb and 8.5% had HCV RNA of 1,556 psychiatric patients [20].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous results showed that the rates of exposure to HBV and HCV infection among psychiatric patients were significantly higher than the estimated general population rates [17][18][19][20][21]. A study by Dinwiddie et al reported that 27.8% patients had HBsAb and 8.5% had HCV RNA of 1,556 psychiatric patients [20].…”
Section: Discussionmentioning
confidence: 98%
“…A study by Dinwiddie et al reported that 27.8% patients had HBsAb and 8.5% had HCV RNA of 1,556 psychiatric patients [20]. In Japan, Sawayama et al studied 196 neuropsychiatric patients and found that 10.2% of the patients were HCV antibody positive compared to 1.5% of controls and 44.4% were HBcAb positive compared to 20.5% of controls [21].…”
Section: Discussionmentioning
confidence: 99%
“…1 Groups of increased risk of infection also include non-intravenous drug users, patients with highrisk sexual practices, and patients admitted to a psychiatric hospital. 11 It is being estimated that the infection is in 65-70% transmitted through injection drug use, 15-20% high-risk sexual behaviors and 5% occupational exposure. 12 Penitentiary institutions have an especially high prevalence of HCV, even 17-21% of inmates are infected.…”
Section: Virus Prevalence Risk Factorsmentioning
confidence: 99%
“…In the USA, estimates of HCV infection in cohorts of patients with severe mental illness have ranged from 8.5% to 19.6% (Rosenberg 2001;Dinwiddie 2003). One US study reported that 10.5% of inpatients with psychosis were positive for hepatitis C (Al-Jurdi 2003).…”
Section: Risk Factors For Hcv Infectionmentioning
confidence: 99%
“…Given the observed prevalence of HCV infection in patients admitted with serious mental illness to a US psychiatric hospital, Dinwiddie et al (2003) recommend routine screening as a reasonable option in this population. Such testing, which should target people with risk factors for acquiring HCV, should be accompanied by pre-and post-test counselling, as a diagnosis of HCV infection can have a very negative impact on pre-existing depression.…”
Section: Hcv Diagnosis From a Psychiatrist's Perspectivementioning
confidence: 99%